Facing an uncertain future: A prospective analysis of trade policy on coastal communities in northwest Newfoundland. (July 2020) - Daly, Jack; Chuenpagdee, Ratana
Abstract: The Great Northern Peninsula (GNP) of Newfoundland has undergone much social and economic change since the downturn in the groundfish fishery in the early 1990s. The Canada-EU Comprehensive Economic and Trade Agreement (CETA) has been promoted as one area of opportunity for revitalizing the GNP but the short and long-term effects of the agreement are not yet known. Assessing the impact of CETA on domestic fishery policy and coastal communities requires a comprehensive examination of the region's governance, as well as an understanding of the entire fisheries system. Following interactive governance theory, this study examines how CETA, as a transnational economic institution, interacts with the existing governing systems at the national, provincial, and regional levels. It further explores the effects that this trade agreement might have on the viability of coastal communities in the GNP, given the natural and social characteristics of the fisheries systems. The research reveals that although the principles and policies of CETA do not directly influence fisheries management, it has implications for the governing system of the region. Specifically, CETA affects the function and structure of the governing system through increased market access and domestic policy changes, with the latter contributing to modifying the interactions between the governing system and coastal communities. Further attention is needed on how local and regional governance systems can build capacity to leverage benefits and minimize potential negative impacts from new modern economic institutional arrangements, like CETA. Highlights: Institutional analytical approach investigates governing system compatibility. Fisheries are susceptible to changes from international trade policies. Canada-EU comprehensive economic and trade agreement has implications for domestic fisheries policy. Domestic fishery protections are necessary to limit consequences of free trade.